(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, the theoretical-methodological foundations of the development of analytical thinking in future pedagogues through the hypothetical-deductive method, and the effectiveness of the dialectical method in the development of analytical thinking are considered high. In the pedagogical process, it is important to teach the common use of thinking styles.